2008
DOI: 10.1016/j.bbrc.2008.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Transient HMGB protein interactions with B-DNA duplexes and complexes

Abstract: HMGB proteins are abundant, non-histone proteins in eukaryotic chromatin. HMGB proteins contain one or two conserved "HMG boxes" and can be sequence specific or nonspecific in their DNA binding. HMGB proteins cause strong DNA bending and bind preferentially to deformed DNAs. We wish to understand how HMGB proteins increase the apparent flexibility of non-distorted B-form DNA. We test the hypothesis that HMGB proteins bind transiently, creating an ensemble of distorted DNAs with rapidly-interconverting conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
15
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
5
15
1
Order By: Relevance
“…Quantifying this change with increasing protein concentrations reveals the binding affinity, and can also provide insight into the specific binding mode. In the case of HMG, average induced bending angles were determined from changes in the persistence length [12], and were in good agreement with other results, including direct visualization methods of AFM [13], as well as cyclization measurements that clearly demonstrate an increase in apparent DNA flexibility induced by these proteins [14]. Distributions of the bending angles seen in AFM experiments further reveal that this change in the persistence length is driven by a combination of discrete bends (static kinks), and increased flexibility at the binding site (flexible hinges) [13].…”
supporting
confidence: 70%
“…Quantifying this change with increasing protein concentrations reveals the binding affinity, and can also provide insight into the specific binding mode. In the case of HMG, average induced bending angles were determined from changes in the persistence length [12], and were in good agreement with other results, including direct visualization methods of AFM [13], as well as cyclization measurements that clearly demonstrate an increase in apparent DNA flexibility induced by these proteins [14]. Distributions of the bending angles seen in AFM experiments further reveal that this change in the persistence length is driven by a combination of discrete bends (static kinks), and increased flexibility at the binding site (flexible hinges) [13].…”
supporting
confidence: 70%
“…In this paper we have studied similar “facilitated dissociation” effects driven by solution phase DNA segments; the presence of DNA segments accelerates the release of pre-bound Fis from a DNA molecule in the manner of “direct transfer” reactions studied for other proteins exchanging between nucleic acid molecules 10; 12; 13; 14; 15; 16; 17; 18; 19; 20; 21; 22; 23; 24; 25; 26; 27; 28 . We have done most of our experiments using the DNA-compacting effect of Fis as a readout of binding (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Double-helix to double-helix “direct transfer” processes have been observed for a variety of DNA-binding ligands and proteins, including ethidium bromide 13; 14 , bacterial transcription factors CAP and Lac repressor 15; 16 , restriction enzymes 17 , eukaryote transcription factors 18; 19; 20 , HMGB proteins 21 , and histones 22; 23 . Direct transfer kinetics also have been observed for transfer of proteins between ssDNA segments, notably for RecA 24 and SSB 25; 26; 27 .…”
Section: Introductionmentioning
confidence: 99%
“…switching between a bent FRET state and an unbent FRET state on a single molecule of DNA over time was seldom observed). Some studies have shown that DNA binding by HMGB1 is dynamic in vitro [30,31] and also in cells [32], while other studies measured slower rates of dissociation [33]. A recent single molecule kinetic study using optical tweezers proposed that microscopic and macroscopic dissociation constants control interactions between HMGB proteins and DNA [34].…”
Section: Discussionmentioning
confidence: 99%